Przez oświatę do wolności. Inicjatywy oświatowo-kulturalne Towarzystwa Polskiego Bratniej Pomocy i Czytelni Polskiej w Czerniowcach w drugiej połowie XIX i na początku XX wieku - Barnaś-Baran, Ewa (Studia Edukacyjne, 2021)
The aim of the article was to show examples of the cultural and educational activities of the Polish Brotherly Aid and Polish Reading Society in Chernivtsi. It started its activity in March 1869 and continued it in the following decades. It combined the task of providing material aid to the Poles living there with activities aimed at counteracting their denationalization. The analysis of source materials made it possible to identify those forms of activity which were defined as moral assistance. It played an important role as the first such association, uniting many people in their concern to preserve their national identity and fight against enslavement. The premises of the Society also unite representatives of national minorities nowadays.